Geopolymer synthetized from sludge residue pretreated by the wet alkalinizing method: Compressive strength and immobilization efficiency of heavy metal. (10th May 2018) - Sun, Shichang; Lin, Junhao; Zhang, Peixin; Fang, Lin; Ma, Rui; Quan, Zonggang; Song, Xin
Highlights: Wet alkalinizing treatment of sludge residue reduced the particle size by 400 times. Pretreatment of sludge residue enhanced the compressive strength of geopolymer. Content of sludge residue determined the characteristic of geopolymer synthetized. Immobilization efficiencies of Cu and Zn in the geopolymer reached more than 95%. Abstract: To realize the reclamation of the sludge residue, we used the sludge residue pretreated by the wet alkalinizing method to prepare geopolymer. Results showed that, when the dosage of the alkali activator, the silicate modulus of the alkali activator, and the doping amount of the pretreated sludge residue were 82.5%, 1.3 mol/mol, and 20% respectively, the compressive strength of geopolymer reached a maximum at 89.03 MPa. The preparation of geopolymer also realized a highly-efficient immobilization of the unstable-forms of copper and zinc (72.22% and 68.60%) in sludge residue, which significantly reduced the pollution risks of the leaching of heavy metals.